Blood flow problem in the presence of magnetic particles through a circular cylinder using Caputo-Fabrizio fractional derivative - Uddin, Salah; Mohamad, Mahathir; Khalid, Kamil; Abdulhammed, Mohammed; Rusiman, Mohd Saifullah; Che-Man, Norziha; Roslan, Rozaini (2018)
In this paper, the flow of blood mixed with magnetic particles subjected to uniform transverse magnetic field and pressure gradient in an axisymmetric circular cylinder is studied by using a new trend of fractional derivative without singular kernel. The governing equations are fractional partial differential equations derived based on the Caputo-Fabrizio timefractional derivatives NFDt. The current result agrees considerably well with that of the previous Caputo fractional derivatives UFDt.